Structural interconversions of the anaphase-promoting complex/cyclosome (APC/C) regulate cell cycle transitions. (April 2020) - Barford, David
Highlights: The APC/C is a large multi-subunit complex that regulates cell cycle transitions through structural changes. Structural changes involve changes in the subunit composition of the complex and by reversible protein phosphorylation. Changes in the subunit composition of the complex are facilitated by a common set of SLIMS shared by substrates, coactivators, E2s and inhibitors. Abstract : The anaphase-promoting complex/cyclosome (APC/C) is a large multi-subunit complex that functions as a RING domain E3 ubiquitin ligase to regulate transitions through the cell cycle, achieved by controlling the defined ubiquitin-dependent degradation of specific cell cycle regulators. APC/C activity and substrate selection are controlled at various levels to ensure that specific cell cycle events occur in the correct order and time. Structural and mechanistic studies over the past two decades have complemented functional studies to provide comprehensive insights that explain APC/C molecular mechanisms. This review discusses how modifications of the core APC/C are responsible for the APC/C's interconversion between different structural and functional states that govern its capacity to control transitions between specific cell cycle phases. A unifying theme is that these structural interconversions involve competition between short linear sequence motifs (SLIMs), shared between substrates, coactivators, inhibitors and E2s, for their common binding sites on the APC/C.